Pregunta
upstudy study bank question image url

In a quadratic rumber puttern, it is given that the seeend constont difference is -6 , the first term is 1 and the fifth term is -55 . Oetermine the geveral formula in this form \( h=a n^{2}+b n+c \).

Ask by Page Williams. in South Africa
Feb 09,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The general formula for the sequence is \( h(n) = -3n^2 + 4n \).

Solución

We are given that the general term of the sequence is h(n) = a·n² + b·n + c. Step 1. Since the sequence is quadratic, its second differences are constant and equal to 2a. We are told the second constant difference is –6, so:   2a = –6  ⟹  a = –3 Step 2. The first term (when n = 1) is 1, so:   h(1) = –3·(1)² + b·1 + c = –3 + b + c = 1   This gives: b + c = 4                     (1) Step 3. The fifth term (when n = 5) is –55, so:   h(5) = –3·(5)² + b·5 + c = –75 + 5b + c = –55   This gives: 5b + c = 20                     (2) Step 4. Subtract equation (1) from equation (2):   (5b + c) – (b + c) = 20 – 4   4b = 16  ⟹  b = 4 Step 5. Substitute b = 4 back into equation (1):   4 + c = 4  ⟹  c = 0 Thus, the general formula is:   h(n) = –3n² + 4n This is the formula for the quadratic sequence with the provided conditions.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To derive the general formula \( h = an^2 + bn + c \), we know that the second constant difference is -6, which tells us that \( a = -3 \) (since the second difference is equal to \( 2a \)). So we have \( h = -3n^2 + bn + c \). We can use the given terms to find \( b \) and \( c \). Given that the first term \( h(1) = 1 \), we can set up the equation: \[ -3(1)^2 + b(1) + c = 1 \implies -3 + b + c = 1 \implies b + c = 4. \] Next, for the fifth term \( h(5) = -55 \), we have: \[ -3(5)^2 + b(5) + c = -55 \implies -75 + 5b + c = -55 \implies 5b + c = 20. \] Now we have a system of equations: 1. \( b + c = 4 \) 2. \( 5b + c = 20 \) Subtracting the first from the second gives: \[ 4b = 16 \implies b = 4. \] Substituting \( b = 4 \) back into the first equation gives: \[ 4 + c = 4 \implies c = 0. \] Thus, the general formula we are looking for is: **\( h = -3n^2 + 4n \)**. This quadratic formula encapsulates the upward mountain we can climb through our number pattern!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad